Optimalisasi Search Engine Optimization untuk Peningkatan Bisnis Frozen Food PT OSB - Setyawati, Diyah Pertywi; Fitriyani, Nurul; Devi, Baisati Mariam; Siroj, Sayyid Agil; Zebua, Sukriyadin; Herlina, Andiani; Taufiqurrahman, Muhammad; Putra, Bihmuyidin Colisna; Saputra, Heri; Mariam, Iis (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service was conducted through Field Experience Practice (PPL) at PT. Optimis Sejahtera Bersama (OSB) with the aim of analyzing and implementing Search Engine Optimization (SEO) strategies to increase the visibility of the frozen food product business. The background of this activity was the company's suboptimal utilization of the digital market. The method used was Participatory Action Research (PAR) with direct practice on On-Page SEO optimization, such as keyword research, writing SEO-friendly content, and internal linking. The results showed that consistent application of SEO on content quality and website structure can improve rankings in search engines. However, there are still obstacles such as fierce competition, changes in Google algorithms, and poor User Experience (UX). This activity recommends periodic SEO audits and ongoing strategy adjustments so that PT. OSB can increase competitiveness, attract organic traffic, and achieve sustainable digital business growth.